The Relationship Between Leg Muscle Power and Shooting Performance in Soccer Among 10th Grade in Senior High School - Palupi, Muhamad Reza Palupi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study investigates the relationship between leg muscle strength and shooting accuracy in soccer among 10th-grade students at Senior High School 1 Pagelaran using a quantitative correlational design. The population consisted of all 10th-grade students participating in physical education, with a purposive sample of 36 students. Data were collected using a leg dynamometer to measure leg strength and a partitioned goal test to assess shooting accuracy. The data were analyzed using the Pearson Product Moment correlation test with SPSS version 27 after fulfilling normality and linearity requirements. The results revealed a very strong and significant correlation between leg muscle strength and shooting accuracy, with a correlation coefficient (r) of 0.925 and a significance value of 0.000 < 0.05. These findings suggest that students with greater leg muscle strength demonstrate higher shooting accuracy in soccer, supporting the biomechanical theory that leg strength contributes to power generation, stability, and ball control during kicking. Thus, it can be concluded that leg muscle strength plays a crucial role in enhancing shooting accuracy. The findings are expected to assist physical education teachers in designing structured training programs to improve students’ soccer performance.